The Use of Allegory in Mystical Literature – Dari Persian Language - Enayatullah Dadman; Abdul Matin Rashidi; Shahwali Shahab (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Allegory, as a sensory mode of imagination and an advanced form of simile, functions in mystical literature not only as a vehicle for conveying metaphysical meanings but also as a subtle medium for reflecting social realities. This study aims to examine how allegorical expressions in the mystical poetry of Sanaee, Attar, and Rumi simultaneously communicate spiritual teachings and encode the socio-historical contexts of their respective periods. Employing a qualitative textual analysis and comparative literary method, the research analyzes selected allegorical narratives, symbols, and thematic motifs in major mystical works, focusing on the relationship between abstract mystical concepts and their concrete narrative representations. The findings reveal that although mystical literature prioritizes the supremacy of the unseen world over the material realm, the poets’ reliance on familiar stories, everyday imagery, and culturally embedded symbols demonstrates a conscious engagement with the social experiences, ethical concerns, and intellectual climates of their audiences. Consequently, allegory emerges as a tangible simile through which abstract spiritual truths are made accessible, while simultaneously allowing readers to discern the poets’ social realities as refracted through personal mystical experience and collective cultural consciousness.